Inequalities in responses to school closures over the course of the first COVID-19 lockdown - Sarah Cattan; Christine Farquharson; Sonya Krutikova; Angus Phimister; Adam Salisbury; Almudena Sevilla (Institute for Fiscal Studies (IFS), 2021)
In England, school closures due to the COVID-19 pandemic represented a sudden but relatively long-lasting shock to children's education. During the first lockdown, schools were closed to all but the most vulnerable children and those with key worker parents from 23 March to the end of May; theybegan to reopen in June and July, but some children remained out of the classroom until September. In this paper, we follow a panel of children between April/May and June/July 2020 to document how home learning experiences changed over the course of the first lockdown, and how these changes were influenced by the partial and voluntary return to school over this period. We find little evidence that children adapted to home learning over the course of the lockdown; instead, learning time fell among those who were not offered the chance to return to school. Pupils who returned to school saw their learning time rise substantially, even conditional on observable and unobservable characteristics. However, while the opportunity to return to in-person schoolingat least part-time was relatively evenly distributed, better-off parents were around 50% more likely to send their children back to school when given the choice. Since better-off students also increased their learning time by more when they returned to school, our results suggest that substantial targeted support will be needed to help disadvantaged pupils catch up, even after all children are back in the classroom.
Keywords: 330; Schüler; Schule; Coronavirus; Epidemie; Infektionsschutz; Fernunterricht; Bildungsertrag; England